Smart Health Monitoring: Detak Jantung Berbasis IoT Menggunakan ESP32 - Jimmie .; Azkhan Azka Safitri Syis Aulia; Muhammad Wahyu Hidayat (Prodi Sistem Informasi Universitas Dharma Andalas, 2026)
This research was motivated by the need for an Internet of Things (IoT)-based heart rate monitoring system that is capable of working in real-time and has a level of accuracy comparable to standard medical devices, because previous research still focused on functional aspects without in-depth quantitative analysis. The purpose of this research is to design and implement an IoT-based smart health monitoring system using an ESP32 microcontroller and a MAX30100 sensor for real-time heart rate monitoring and to evaluate system performance. The method used is a prototype method that includes the stages of communication, quick plan, modeling quick design, construction of prototype, and deployment delivery and feedback. The analysis technique used is a descriptive analysis of test data by observing heart rate (BPM) and oxygen levels (SpO?), then classifying the user's condition into normal, low, or high categories based on predetermined standards. The results of the study show that the system is able to read, display, and transmit heart rate data in real-time through the Blynk application and provide automatic notifications via Telegram. In addition, the system can classify user conditions well so that it can be used as a practical and effective solution for independent and remote heart health monitoring.